Tindak Tutur Representative dalam Video Soal UTBK 2025 Penalaran Umum Bagian 1 dan 2 pada Kanal Youtube Privat Al Faiz (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
The use of digital media such as YouTube now serves not only as a means of entertainment but also as an interesting educational interaction space to be studied from a pragmatic perspective. This study aims to describe the forms and functions of representative speech acts in the 2025 UTBK General Reasoning Questions Parts 1 and 2 videos on the Privat Al Faiz YouTube channel. This study uses a pragmatic approach with a qualitative descriptive method. Data were collected through free listening and note-taking techniques, then analyzed using matching and distribution methods to identify the context, illocutionary meaning, and function of each representative speech act, which were then presented in both formal and informal formats. The analysis identified 218 representative speech acts across eight types: explaining, stating, informing, mentioning, suggesting, acknowledging, giving examples, and speculating. The most dominant types were explaining and stating because they served to clarify the material and guide the audience to understand the logical flow of reasoning. These findings show that representative speech acts in digital learning do not merely convey information but also play a role in building reflective instructional communication between teachers and students. Theoretically, this study enriches pragmatic studies in the realm of digital discourse, while practically, it can be a reference for educators in developing effective and adaptive communication strategies for the development of educational technology.